ANALISISS PELAKSANAAN PELAYANAN HANDLING COMPLAINT BERDASARKAN PERSPEKTIF PETUGAS DAN PASIEN DI RUMAH SAKIT - Sely Aprianda Syah Putri; Joko Kismanto; Hasna’ Nisa Ul Mufidah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Complaint handling in hospitals plays an important role in maintaining the quality of medical services and improving patient satisfaction. Data from the Ministry of Health (Kemenkes) shows that over the past two years, patient complaints have increased by 15% in various health facilities. Hospitals with responsive complaint teams can increase patient satisfaction by up to 25%, which has a positive impact on the hospital's image. Data from the 2018 Basic Health Survey (Riskdas) shows that 40% of hospitals in Indonesia do not yet have consistent standard procedures for handling complaints. This study aims to analyze the implementation of complaint handling in hospitals by examining the perceptions and experiences of staff and patients in order to provide appropriate recommendations for improving the hospital complaint management system. The type of research used in this study is a mixed method with a cross-sectional research design. The results show that the stages of complaint handling are procedurally in place but have not been implemented consistently. Most officers stated that the reporting system was easy to use (75%), but only 25% had ever attended training. From the patient's perspective, the indicator with the highest satisfaction was the empathy and communication of staff (71.1%), while fairness in complaint resolution received the lowest score (58.9%). Bivariate analysis showed a significant relationship between perceptions of complaint handling and patient satisfaction (p=0.022; RP=2.784). The main obstacles for staff were high workloads and lack of training, while patients complained about lack of transparency and fear of voicing complaints. There is a perception gap between staff and patients regarding the complaint system. Strengthening training, workload management, and system transparency is essential to improve customer trust and satisfaction.Keywords: Handling Complaint, Service Quality